PERAN GREEN MARKETING, GREEN BRAND IMAGE TERHADAP PURCHASE INTENTION DENGAN GREEN TRUST SEBAGAI VARIABEL INTERVENING - Yahya, Yahya (Jurnal Ilmiah Manajemen dan Bisnis (JIMBis), 2022)
The concept of green marketing in the company as a form of attention to environmental damage issues. The company then developed to find the right marketing strategy in growing purchase intention. The bottled drinking water industry (AMDK) is one who develops green marketing. This study aims to analyze the effect of green marketing and green brand image on purchase intention through green trust, and to analyze the effect of green marketing, green brand image and green trust on purchase intention. This research uses a questionnaire measured by a Likert scale, find the sample using a non-probability method with a procedure by using purposive sampling. The total respondents in this study were 100 respondents who were consumers who had purchased Cleo bottled water. Data analysis method using partial least squares (PLS) analysis with SmartPLS software. The results reveal that green marketing and green brand image have an effect on purchase intention through green trust on Cleo bottled water products, green marketing and green trust have an effect on purchase intention on Cleo bottled water products, and green brand image has no significant effect on purchase intention on products. Cleo's AMDK.